1996
DOI: 10.1136/thx.51.4.411
|View full text |Cite
|
Sign up to set email alerts
|

Acute asthma during pregnancy.

Abstract: Background -Acute asthma during pregnancy is potentially dangerous to the fetus. The aim of this study was to investigate the effect of an acute attack of asthma during pregnancy on the course of pregnancy or delivery, or the health of the newborn infant, and to identify undertreatment as a possible cause of the exacerbations. Methods -Five hundred and four pregnant asthmatic subjects were prospectively followed and treated. The data on 47 patients with an attack ofasthma during pregnancy were compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
1
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(91 citation statements)
references
References 8 publications
2
85
1
3
Order By: Relevance
“…The same group performed another study of 504 pregnant females with asthma and found that females who had an acute attack during the pregnancy were less likely to have been using ICS prior to the attack [23]. However, there was no difference in pregnancy outcomes, including length of gestation and birth weight in females who had an acute attack, compared with both the control group and those who did not have an acute attack during pregnancy.…”
Section: Prospective Cohort Studiesmentioning
confidence: 95%
See 1 more Smart Citation
“…The same group performed another study of 504 pregnant females with asthma and found that females who had an acute attack during the pregnancy were less likely to have been using ICS prior to the attack [23]. However, there was no difference in pregnancy outcomes, including length of gestation and birth weight in females who had an acute attack, compared with both the control group and those who did not have an acute attack during pregnancy.…”
Section: Prospective Cohort Studiesmentioning
confidence: 95%
“…However, there was no difference in pregnancy outcomes, including length of gestation and birth weight in females who had an acute attack, compared with both the control group and those who did not have an acute attack during pregnancy. The authors suggest that prompt treatment of these patients with ICS contributed to the positive outcome [23]. A disadvantage of these studies was their ''mixed cohort'' nature, with the asthmatic group being prospectively recruited and followed, and the control group data being retrospectively collected from medical records.…”
Section: Prospective Cohort Studiesmentioning
confidence: 99%
“…[4][5][6][7][8] Larger studies, however, have identifi ed fewer signifi cant adverse obstetric outcomes. 1,9,10 A multicenter prospective observational cohort study performed by the Maternal-Fetal Medicine Units Network evaluated the relationship between asthma severity and maternal and fetal morbidity among pregnant women with asthma and matched controls. 11 This study demonstrated a strong relationship between asthma severity and exacerbation during pregnancy, as well as associations with nonpulmonary pregnancy outcomes, including cesarean delivery, preeclampsia, gestational diabetes, and Background: The article was designed to estimate the effect of active and passive household cigarette smoke exposure on asthma severity and obstetric and neonatal outcomes in pregnant women with asthma.…”
mentioning
confidence: 99%
“…A asma é classificada em leve (intermitente ou persistente), moderada e grave 2 e as exacerbações graves podem ocorrer em qualquer uma destas formas, sendo mais freqüentes nos casos de asma moderada e grave, em que também são mais freqüentes as complicações perinatais 3 . Vários estudos têm demonstrado um aumento na incidência de complicações perinatais decorrentes da associação de asma e gravidez, que parecem ser mais freqüentes nos casos mal controlados [8][9][10][11][12] . As complicações mais comuns são o aumento da mortalidade perinatal, placenta pré-via, pré-eclampsia, parto prematuro, anomalias congênitas, baixo peso ao nascer e aumento da incidência de cesárea.…”
Section: Introductionunclassified